Communication Strategy of Mangrove Rehabilitation in Muara Gembong, Bekasi District – West Java - Rici Tri Harpin Pranata; Arif Satria; Tri Budiarto; Willy Bachtiar; Nur Hannah Muthohharoh (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
Mangrove ecosystem rehabilitation is one of the strategic agendas for blue carbon climate change mitigation. Environmental communication studies are crucial in advancing mangrove ecosystem rehabilitation by facilitating collaboration among diverse stakeholders with varying roles and interests. Grounded in fostering mutual understanding, environmental communication aims to enhance dialogue and engagement in conservation. Therefore, this research aims to analyze 1) the effectiveness of environmental communication strategies in the mangrove ecosystem rehabilitation and 2) factors that influence the effectiveness of environmental communication of the mangrove ecosystem rehabilitation. This research was conducted in Muara Gembong District, Bekasi Regency, West Java. This research employs quantitative and qualitative methods. This research shows that in developing persuasive communication of the mangrove rehabilitation agenda, the two-way communication model is most effective in fostering an attitude of altruism in preserving the environment. In the digital technology development era, face-to-face communication has become the most effective choice for communicating with people with limited access to digital infrastructure and low literacy. Message senders often ignore evaluations to assess the effectiveness of communication. Evaluation will encourage improvement and continuity of communication until the expected impact can be achieved.